Membangun Literasi Informasi Perpustakaan melalui Pendidikan Pemakai - Sukirno, Sukirno (Pustakaloka, 2009)
Nowadays, the society still take advantage of library rarely. It is shown by a small numberÂ  visitorsÂ  who take advantage of references collection. One of the factors that cause this fact is literacu of society which means and ability to know, to evaluate and to use the needed information effectively. The literacy can be formed by user education program that firstly acquaints the user about the vast of library collection, services and informational material available for them, and secondly teaches how the attain those library banefits so they are able to search information and uis it correctly.